A review on reactivity characteristics and synergy behavior of biomass and coal Co-gasification. (13th May 2021) - Wei, Juntao; Wang, Miao; Wang, Fuchen; Song, Xudong; Yu, Guangsuo; Liu, Yurong; Vuthaluru, Hari; Xu, Jie; Xu, Yin; Zhang, Hong; Zhang, Shu
Abstract: Co-gasification is a promising approach to the clean and high-efficiency co-utilization of biomass and coal with syngas (H2 +CO) production. Gasification reactivity is an important factor influencing the operation conditions choice, carbon conversion efficiency and syngas production performance. Coal-biomass interaction during co-gasification will directly result in the synergy behavior of different forms and intensities on co-gasification reactivity. Due to the fuel origin diversity, structural property difference and reaction process complexity of biomass and coal, a clear understanding of reactivity characteristics and synergy behavior of co-gasification is very essential for revealing co-gasification reaction mechanism and providing theoretical support for actual application. In this paper, the influences factors (such as feedstock type, blended ratio, gasification temperature, co-pyrolysis process, gasification reactor and biomass pretreatment) for co-gasification reactivity and the synergy behavior on co-gasification reactivity are summarized in details, and non-catalytic/catalytic synergy mechanisms for co-gasification are discussed. Previous researchers have acquired a plenty of meaning data, providing important reference for industrial application of co-gasification technology. However, volatile matter-char interaction mechanism during co-pyrolysis was still unclear, AAEM migration and transformation route during co-gasification are lack of in-situ analysis, transfer route and interaction of free radicals during co-gasification process were unknown, and co-gasification kinetics model containing dynamic synergistic/inhibition factors hasn't been established. Highlights: Influences of different factors on co-gasification reactivity and synergy are reviewed. Catalytic/non-catalytic synergy mechanisms of biomass and coal co-gasification are described. Future perspectives on co-gasification are proposed based on the current research progress.